2021
DOI: 10.3389/fimmu.2021.626017
|View full text |Cite
|
Sign up to set email alerts
|

OX40L/OX40 Signal Promotes IL-9 Production by Mucosal MAIT Cells During Helicobacter pylori Infection

Abstract: Mucosal associated invariant T (MAIT) cells play a critical role in Helicobacter pylori (H. pylori)-induced gastritis by promoting mucosal inflammation and aggravating mucosal injuries (1, 2). However, the underlying mechanism and key molecules involved are still uncertain. Here we identified OX40, a co-stimulatory molecule mainly expressed on T cells, as a critical regulator to promote proliferation and IL-9 production by MAIT cells and facilitate mucosal inflammation in H. pylori-positive gastritis patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In addition, no differences in gastric Vα7.2 + CD161 hi T cell frequencies between H. pylori-infected and H. pylori-uninfected groups were observed despite being the local area of infection; and this may be due to our limitation of our sample population in that all gastric samples had gastritis. 6,7 Nonetheless, Ming et al 65 have shown that MAIT cells produce high levels of IL-9 and these IL-9-producing MAIT cells are related to H. pylori-infected individuals, of which all had gastritis, further suggesting MAIT cell relation to H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no differences in gastric Vα7.2 + CD161 hi T cell frequencies between H. pylori-infected and H. pylori-uninfected groups were observed despite being the local area of infection; and this may be due to our limitation of our sample population in that all gastric samples had gastritis. 6,7 Nonetheless, Ming et al 65 have shown that MAIT cells produce high levels of IL-9 and these IL-9-producing MAIT cells are related to H. pylori-infected individuals, of which all had gastritis, further suggesting MAIT cell relation to H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal mononuclear cells were isolated from the gastric mucosa biopsy of the patients as previously described ( 4 ). Briefly, biopsy specimens were digested with shaking at 37°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded samples were cut into 5-μm slices, and immunohistochemistry was conducted as previously described ( 4 ). In brief, the mucosa was fixed with paraformaldehyde, followed by antigen retrieval with the EDTA antigen retrieval solution (Servicebio).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations